(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This aim of this research was to 1) Study the operational process of the community financial institution, 2) Study the condition of using information technology in the community financial institutions, 3) Develop guidelines for the application of information technology, in the development of the community financial institution. This research was carried out by using a joint combination of quantitative samples, which includes 240 members of the community financial institution and a qualitative sample, which includes 30 people from the administrative and staff of the community institution. In terms of data collection, this research collected their data with questionnaires, interviews, and observations and group discussion. The data were analyzed to find the frequency, percentage, text synthesis and content analysis. The result of this researched showed that: 1) The result of data analysis on the operational process of the community financial institution was divided into 4 parts such as; 1) savings - deposit 2) loan and lending 3) Management of compensation and benefits 4) Management of the community financial institutions. 2) The condition of using information technology in the community financial institution, both hardware, and software were been supported by the bank in charge, but still not enough in terms of usage. Some staff still lack adequate knowledge, and skill for information technology. 3) Develop guidelines for the application of information technology for the development of community financial institutions. This was summarized into 3 issues: 1) In terms of hardware, they should be effective, efficient and suitable for work, they should also be sufficient for work. 2) In terms of software, they should be up to date developed software, responds to all segment of work levels. 3) In terms of personnel, the staffs should be encouraged and developed to gain more continuous knowledge and ready for work.